Biografi dan Pemikiran Dakwah Anregurutta K. H. Abdurrahman Ambo Dalle - Muh. Yahya Saraka (Dakwah Institut PTIQ Jakarta, 2022)
This study aims to see and explore the biography, thoughts, and social, political, and religious conditions of Anregurutta K. H. Abdurrahman Ambo Dalle, who is a charismatic cleric from South Sulawesi. He lived in three generations or ages; First during the Dutch occupation; Second, the Japanese occupation; Finally, the early days of Indonesian independence. This study uses a qualitative approach, with the Biography method, which is to describe and describe the life history, thoughts, and socio-political conditions of Anregurutta. The data collection technique used in this research is reference and library search, which is the activity of collecting materials related to research from books, scientific journals, literature and other publications that are worthy of being used as sources for research to be carried out. carefully the author, by describing and describing the data is through several expert opinions. The author found that Anregurutta K. H. Abdurrahman Ambo Dalle was one of the propagators of Islam and the second generation of ulama after three Datuks from Miangkabau came to spread Islam in South Sulawesi. His thoughts use a cultural da'wah approach that adapts to the conditions of Bugis customs and culture, so that it is easily accepted by the community.